Sosialisasi Kepatuhan dan Kesadaran Hukum di Desa Bila, Kecamatan Sabbangparu, Kabupaten Wajo - Andi Bau Mallarangeng; Mustari; Andi Wahyuddin Nur; Besse Nurfatimah; Selfiana; Gustina; Fatur Rahmatullah; Muhammad Bayu Aprilian Chandra (YP-SDI Lamaddukelleng, 2025)
In Indonesia, various studies have shown that there is still a significant gap in public understanding of applicable laws and regulations, especially in rural or remote areas such as Bila Village. Therefore, efforts to bridge this gap require socialization of legal compliance and awareness in Bila Village, Sabbangparu District, Wajo Regency as a form of community service aimed at increasing public compliance and awareness. This socialization method is considered very effective in internalizing the law in the community to ensure that the law is not only known, understood and internalized but also respected and obeyed.